The Effectiveness Of The "BANDREC" Teaching Material Based On The RADEC Learning Model In Improving The Cultural And Civic Literacy Of Phase A Students On The Material On Pancasila Values And Symbols - Wizaksana, Hamba; Sutarsih, Cicih (International Conference on Elementary Education, 2025)
This study aims to examine the effectiveness of the "BANDREC" teaching materials based on the RADEC learning model in improving cultural and civic literacy among Phase A students in the subject of Pancasila values and symbols. The method used is a quantitative pre-experimental study with a one-group pretest-posttest design. The research subjects were second-grade elementary schoolstudents in Bandung. The results showed a significant improvement in students' cultural and civic literacy after using the "BANDREC" teaching materials. The average pre-test score of 28.22 increased to 70.78 in the post-test. Statistical analysis indicates that teaching materials based on the RADEC learning model are effective in enhancing students' understanding of Pancasila values and symbols. These findings suggest that the use of interactive RADEC-based teaching materials can serve as a relevant learning strategy to strengthen students' cultural and civic literacy